An improved capacitor voltage full feedforward control strategy for LCL‐type grid‐connected inverter based on control delay compensation - Xingwu Yang (Wiley, 2021)
Abstract For the LCL‐type grid‐connected inverter, when the capacitor voltage feedforward is applied, the delay in the digital control system could change the phase characteristics of capacitor voltage feedback and affect the stability of the system. To solve the problem, a delay compensation method based on lead compensator is proposed in this paper, which can reduce the impacts of control delay on the capacitor voltage full feedforward control system. In this study, a lead compensator is introduced into the feedforward channel to compensate the phase lag, and the compensation function is designed to compensate for the phase margin but not change the system amplitude gain. The proposed strategy can keep the phase margin of the system above 25° when the grid impedance changes from 0 to 2.6 mH (0.1 p.u.), which enhances the robustness of the grid‐connected inverter under weak condition. The grid current distortion caused by grid background harmonics is greatly reduced and is kept within 4%. Moreover, the proposed strategy has fast dynamics while ensuring the system stability. Finally, the simulation and experimental results are presented to verify the effectiveness and robustness of the proposed control strategy.